The Peasants’ Savings and Loans Societies in Lithuania Before the First World War - Mačiekus, Venantas; Pladis, Benjaminas (Ekonomika, 1997)
The first savings bank in the territory of present-day Lithuania was founded approximately in 1830 in Klaipėda. The first credit union was already functioning in Šilutė in 1865. These towns belonged 10 Germany at that time. Some years later credit unions also appeared in another part of Lithuania, the region that belonged to Russia. For example, the first peasant savings and loan societies were established in the Kaunas district only in 1873. Before the First World War these societies accumulated approximately 4 million roubles of credit resources. These credit resources could only amount to 20–25 percent of all Lithuanian peasants’ savings.